HUBUNGAN KONTAMINASI COLIFORM DAN SKOR PERILAKU HIGIENE-SANITASI PADA PEDAGANG JAJANAN DI KANTIN SEKOLAH DAN PEDAGANG KELILING[Correlation between Nutritional Status and Magnesium Intake towards Premenstrual Syndrome (PMS) in Female Teenagers] - Andhita Riana; Sri Sumarmi (Media Gizi Indonesia, 2018)
Food is one  of components that can cause illness, so it must be safe. An outbreaks of food poisoning 19% happened  in school and 78.57%   happened to elementary   school children. Hygiene and sanitation are important factors related to food safety. This study was aimed to analyze correlation between behavior of hygiene and sanitation of food vendors with food safety by using most probable number of coliform indicator. This was an observational study used cross sectional design, involving 25 food  vendors and 25 food sample which were selected randomly. Result showed  that 40% of the snacks were contaminated by Coliform (>10 Juml./g). The highest contamination of Coliform was >1.100 Juml./g and was found on four food snacks sold in the canteen. Categories of hygiene knowledge score of vendors ware moderate (52%). The majority of vendors ware included in the moderate hygiene attitude score category (52%), and most of the vendors ware included in the moderate hygiene practice score category and moderate environment sanitation score category (56%, respectively). Statistical analysis using Spearman’s rho test showed that there ware a significant correlation  between knowledge of hygiene, practice of hygiene, and environment sanitation of vendors with food safety using indicator most probable number of coliform (p=0.022, p=0.005, p=0.000, respectively). Whereas no significant correlation found between  attitude of hygiene with contamination of Coliform (p=0.088). It was Found as much as 40% of foods are contaminated by coliform  and should be awared, observations of food processing needs to be applied to prevent coliform contamination of school children’s snacks.